Being a Professional Teacher in the Era of Industrial Revolution 4.0: Opportunities, Challenges and Strategies for Innovative Classroom Practices - Afrianto Afrianto (English Language Teaching and Research, 2018)
This paper discusses how professional teachers in Indonesia can maintain their professionalism in a rapidly developing world due to the developments caused by the information technology revolution in relation to the industrial world which has led to the rise of so-called industrial revolution 4.0 (IR 4.0). Some characteristics of the IR 4.0 era are digitalization, internets of things, internet of people, big data, iCloud data, and artificial intelligence. All of these new developments have brought about disruption in various sectors of life, including education. The IR 4.0 can be negative, as it can threaten the existence of schools and teachers. Yet, it can also be positive because it brings many opportunities for innovative research and classroom practices which can subsequently accelerate and optimize teachers’ productivity and students’ learning outcomes. Therefore, professional teachers must be aware of and adapt themselves to this development. Teachers of this digital age, for instance, should be teachers with the 21st-century learning mindset, possess digital literacy, keep learning new things, and should able to make use of opportunities provided by the IR 4.0 for their better teaching. Integrating classroom activities with some online platforms through blended/hybrid learning is a highly recommended teaching strategy for today's teachers. In short, if they are carried out consciously and systematically, all developments in the IR 4.0 will certainly have a positive impact on the achievement of our national education goals in the future.Keywords: professional teacher, disruption era, industrial revolution 4.0, blended learning, classroom practices